1995
DOI: 10.1111/j.1600-0722.1995.tb01859.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a sodium hypochlorite treatment on demineralized root dentin

Abstract: The effects of a 10% NaOCl treatment for 2 min on demineralized human root dentin were investigated by means of: microradiography (MR), scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM) and secondary ion mass spectroscopy (SIMS). MR measurements revealed that NaOCl caused a tissue contraction not related to water loss but to removal of organic substance(s), resulting in reductions of the lesion depth and mineral loss values by 15% and 42%, respectively. CLSM observations on wet dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…18 Treatment of the demineralized collagen matrix with a proteolytic agent, such as sodium hypochlorite (NaOCl), may have an additional beneficial effect to these adhesives, facilitating infiltration 19 of the acidic resin monomers into the dentin substrate. [20][21] Alternative bonding strategies, such as multiple applications 22 or increased substrate contact time of the acidic primers, 23 may also be helpful in achieving a better link between the adhesives and dental substrates.…”
Section: -13mentioning
confidence: 99%
“…18 Treatment of the demineralized collagen matrix with a proteolytic agent, such as sodium hypochlorite (NaOCl), may have an additional beneficial effect to these adhesives, facilitating infiltration 19 of the acidic resin monomers into the dentin substrate. [20][21] Alternative bonding strategies, such as multiple applications 22 or increased substrate contact time of the acidic primers, 23 may also be helpful in achieving a better link between the adhesives and dental substrates.…”
Section: -13mentioning
confidence: 99%
“…27 Moreover, as water is required to maintain the collagen in its expanded state, in groups with sodium hypochlorite treatment, removal of the collagen fibers with deproteinizing agents would facilitate the access of resin to a substrate that is more permeable and less sensitive to moisture. 28 The results of this in vivo study demonstrated extensive leakage and generalized gap formation in samples restored with the hybrid composite Spectrum TPH and Prime & Bond NT without any surface treatment in both moist and dry conditions. These results are contrary to the previous in vitro study reporting a significant gap-free attachment of Prime & Bond NT to dentin following the manufacturer's instructions.…”
Section: Discussionmentioning
confidence: 72%
“…Previous observations and preliminary studies in our laboratory indicated that NaOCl also has a considerable capacity to disintegrate carious dentin when applied in a large excess [NordbĂž et al, 1996]. Calcified dentin, on the other hand, does not seem to be significantly altered by NaOCl [Rosenfeld et al, 1978], al-though this perception has recently been called into question [Barbosa et al, 1994;Inaba et al, 1995]. The commercially available product Carisolvℱ (MediTeam AB, Gothenburgh, Sweden) [Ericson et al, 1999], which is based on an NaOCl-containing solution and represents a further development of the former American product Caridexℱ, has the capacity to soften carious dentin.…”
mentioning
confidence: 74%
“…Pronase proved to be more efficient than collagenase and NaOCl at solubilizing carious dentin, although Inaba et al [1995] showed that NaOCl effectively removed organic components from demineralized, noncarious root dentin. A previous investigation in our laboratory also demonstrated that NaOCl and polyacrylic acid in tandem were able to produce apparently clean cavity walls when used following manual excavation of carious dentin [NordbĂž et al, 1996].…”
Section: Discussionmentioning
confidence: 99%